Conflicto y violencia en América VIII Encuentro-Debate América Latina ayer y hoy - DALLA CORTE, Gabriela coord.
Otros descriptores: ARGENTINA; AMAZONIA; AMAZONAS; NEGROS; INMIGRACION; CHIAPAS; GUATEMALA; MIGRACION INTERNACIONAL Y COLONIZACION; ESCLAVITUD; MARGINALIDAD; BRASIL; AMERICA LATINA. Otros colaboradores: GARCIA JORDAN, Pilar; IZARD, Miquel; LAVIÑA, Javier; PISQUERAS, Ricardo; TOUS, Meritxell; ZUBIRI, María Teresa